Die Ou Testament en die Belydenis van Belhar (1986) - Snyman, SD (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The Old Testament and the Confession of Belhar (1986) The use of the Old Testament in the Confession of Belhar is investigated. The fact that there are only four explicit references to the Old Testament in the Confession occurring only in the fourth article on righteousness merits such an investigation. The Old Testament does have a contribution to make on the statements of unity and reconciliation as well. Although the Confession of Belhar does not contradict the teachings of the Old Testament, it is nevertheless a pity that theological insights from the Old Testament do not feature more prominently in die Confession. The result of this investigation shows that theological insights from the Old Testament could also have been used in the other articles of the Confession to strengthen its theological value.